Communication Strategies of the Head of Lingkungan 1 Bahari in Mitigating Youth Social Conflicts Related to the Dangers of Gang Fights - Fatwa Hakim; Nurhanifah (Al Mabhats : Jurnal Penelitian Sosial Agama, 2026)
Communication strategy plays a crucial role in preventing social problems, as it determines how messages are designed, delivered, and received by the target audience. Within a community context, an appropriate communication strategy can foster shared understanding, particularly among adolescents who are vulnerable to social conflict. This study aims to analyze the communication strategies employed by the Head of Neighborhood 1, Bahari, to foster adolescents’ social awareness of the dangers of gang fights in Martubung Village, Medan Labuhan District. A qualitative approach was utilized, employing observation and semi-structured interviews with the neighborhood head and adolescents. The findings indicate that the communication strategy involves clear objectives, identification of appropriate target audiences, persuasive messages, direct communication channels, and a sustained dialogical process. These strategies contribute to improved understanding and positive changes in adolescents’ attitudes toward social conflict. The study confirms that leadership communication strategies at the neighborhood level play an important role in preventing youth brawls and enhancing adolescents’ social awareness.